PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN KANTOR ESTATE (Studi Kasus Pada PT. Daria Dharma Pratama Air Berau Estate) - Merta Kusuma; Sri Ekowati; Ipan Wahyudi (UNIVED Press, 2020)
Merta Kusuma, Sri Ekowati, Ipan Wahyudi; This study aimed to determineThe Effect of Compensation and Motivation toward Employees’ Performanceof Estate Office (A Case Study on PT. Daria Dharma Pratama Air Berau Estate). The population of this study were 40 employees of PT. Daria Dharma Pratama Air BerauEstate. The sampling technique of this study was saturated sampling where all the population was 40 employees. The data collection method was a questionnaire. The data analysis techniques of this research used multiple linear regression, coefficient of determination, and hypothesis testing.The results of the study known that the compensation variable has a significant effect toward the performance of Employees at the Estate Office of PT. Daria Dharma Pratama Air Berau estate. It is seen from a significant value of 0.000 less than 0.05. Motivation is influential because a significant value of 0.002 is smaller than 0.05. The coefficient of determination of R square is 0.698. This means that the Employees’ performance of the Estate Office is 69.8% by the independent variable namely compensation and motivation. While 100-69.8%= 30.2%) are influenced by other causative factors not examined in this study. Keywords: Compensation, Motivation, and Employee Performance.